THE INVOLVING BOARDING SCHOOL IN MENTAL REVOLUTION - Mawardi Lubis (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The objective of this research was to understand the involving boarding school in mental revolution. The approach be used in research was library research with descriptive analysis method. The data were collected through references review those connect to the involving boarding school in mental revolution. The research sample was 4 (four) boarding schools, consist of 1. PP Amanatul Ummah Wonocolo, Surabaya, Jawa Timur 2. PP Suryalaya Godebag, Desa Tanjung Kerta, Pagerageung, Tasikmalaya 3. PP Nurul Barokah Beji, Bojongsari, Purbalingga, Jawa Tengah 4. PP Al-Anwar Sarang, Rembang, Jawa Tengah. The research result indicates that those boarding schools had involved in mental revolution to educate in thousands of students and product graduations those had God’s marcy mental in the word (mental rahmatan lil ‘alamin), good character, as well as glorify divinity and humanity values